A theory of justice - Rawls, John (The Belknap Press, 1971)
John Rawls draws on the most subtle techniques of contemporary analytic philosophy to provide the social contract tradition with what is, from a philosophical point of view at least, the most formidable defense it has yet received ...[and] makes available the powerful intellectual resources and the comprehensive approach that have so far eluded antiutilitarians. Though the "Revised Edition of A Theory of Justice", published in 1999, is the definitive statement of Rawls's view, so much of the extensive literature on Rawls's theory refers to the first edition. This reissue makes the first edition once again available for scholars and serious students of Rawls's work.